A Classroom Action Research: Improving Speaking Skills through Work in Pair Technique - Maya Marsevani; Habeebanisya Habeebanisya (Siliwangi University, 2022)
This Classroom Action Research (CAR) is implemented to improve students’ speaking skills at one of the junior high schools in Batam. The subjects of this research were 32 second-semester students in grade 7. The research was applied in two cycles following the procedures for action research, namely planning, action, observing, and reflecting. The researchers used classroom observation, document analysis, pre-test, and post-test to collect data. The findings show that the Work in Pairs method improves students’ speaking skills in class. This can be seen from the improvement of students' speaking skills in each cycle. The students achieved 57.26 for the pre-test which is categorized poor. After implementing Work in Pairs activities in two cycles the students’ average scores improved. The post-test was 65,33 in the first cycle and 72,93 in the second cycle. This proves that students responded positively to the Work in Pairs method. It can be concluded that working in pairs activities have a strong influence on improving students’ speaking skills.